The Popes, the Catholic Church and the Transatlantic Enslavement of Black Africans 1418-1839 (Volume 16) - Adiele, Pius Onyemechi (Georg Olms Verlag, 2017)
Mehr als 400 Jahre lang erlitten schwarzafrikanische Männer, Frauen und Kinder während des transatlantischen Sklavenhandels schlimmste Formen der Versklavung und Erniedrigung durch Katholiken und das westliche Christentum. Damals wie heute glaubte niemand an die tiefe Verwicklung der Kirche und des Papsttums in den schwarzafrikanischen Holocaust. Trotz jüngster Behauptungen des päpstlichen Officiums in Rom, wonach die Päpste jegliche Form von Sklaverei verurteilten, so auch im Falle der Versklavung von Schwarzafrikanern, verweisen neuere Studien innerhalb dieses Forschungsfeldes auf das Gegenteil. Die Kirche und die Päpste nahmen vielmehr zentrale Rollen in diesem schlimmsten Verbrechen gegen die Schwarzafrikaner seit Beginn der schriftlichen Dokumentation ein. Mithilfe zahlreicher päpstlicher Bullen aus den Geheimarchiven des Vatikans und einer Vielzahl an königlichen Dokumenten aus dem portugiesischen Nationalarchiv in Lissabon, strebt der vorliegende Band eine kritische und analytische Untersuchung dieses Aspekts des transatlantischen Sklavenhandels an, der über so viele Jahre von den westlichen Historikern und Gelehrten verschleiert wurde.For over 400 years, Black African men, women and children suffered the worst type of enslavement and humiliation from the hands of Catholics and other Western Christians during the transatlantic slave trade. Before now, no one could ever believe that the Popes of the Church were deeply involved in this Holocaust against Black African people. Despite the claims made by the hallowed papal office in Rome in recent years that the Popes condemned the enslavement of peoples wherever it existed including that of Black Africans, recent researches in these fields of study have proved the contrary to be true. The Church and her Popes were rather among the major "role players" in this worst crime against Black Africans in recorded history. With the help of a considerable number of papal Bulls from the Vatican Secret Archives and a great amount of Royal documents from the Portuguese National Archives in Lisbon, the present book is aiming to undertake a critical and analytical inquiry of this aspect of the transatlantic slavery that has been kept in the dark for so many years by the Western historians and scholars. The results of this studious but fruitful academic inquiry are laid bare in this notable work of the 21st century. Pius Onyemechi Adiele is a Catholic priest of Ahiara Diocese Mbaise and an alumnus of Seat of Wisdom Seminary Owerri and Bigard Memorial Seminary Enugu in Nigeria. He obtained his licentiate in Theology from the famous University of Münster and his doctoral degree in Church History from the renowned University of Tübingen in Germany. At present, he is a research fellow in the areas of African Church History and Enslavement of peoples as well as the pastor in charge of the merged parishes of Lauchheim, Westhausen, Lippach, Röttingen and Hülen in Germany.